Metal‐Organic Framework‐Based Tribovoltaic Textile for Human Body Signal Monitoring - Yuanlong Li; Yinghong Wu; Alexander V Shokurov; Carlo Menon (Advanced Science)
Abstract The pursuit of sustainable and portable direct current (DC) energy suppliers has ignited considerable interest in tribovoltaic nanogenerators (TVNGs), devices that harvest mechanical energy from the surrounding environment. However, the predominant focus in TVNG research has centered on rigid and silicon‐based semiconductors that lack flexibility and are thus ill‐suited for integration into common fabrics. Herein, a fully‐textile TVNG with a simple design is introduced that enables the real‐time monitoring of human physiological signals. The utilization of copper‐benzenehexathiol (Cu‐BHT), a conductive 2D metal‐organic framework is proposed as a p‐type semiconductor grown on fabric surfaces. The developed tribovoltaic textile (TVT) consists of Cu‐BHT‐modified cotton and metallic aluminum textile producing pure DC output due to self‐rectification. With excellent flexibility and stability, Cu‐BHT TVT is seamlessly integrated into textile‐based accessories for continuous monitoring of human motion and respiration.